TRANSLATING CODE-SWITCHING IN THE INDONESIAN VERSION OF DER BOXER - Salim, Dias R. (International Review of Humanities Studies, 2019)
Code-switching is the use of more than one language in an utterance. Within a narrative work like comics, code-switching can be used to show exoticism, character identity, or dramatic effect. Translating such a speech pattern poses a challenge to a translator. This paper discusses how a translator covert speeches that code-switch to three foreign languages – English, Yiddish, and Hebrew – in the German comic der Boxer by Reinhard Kleist into Indonesian. Translation units such as words, phrases, and sentences in the the target text will be compared to its counterparts in the source text to note the procedures used by the translator. The data gathered will then be analyzed to observe which utterances are kept in their foreign form, kept with additional information, or translated functionally and literally. Each procedure taken has its effects on the target text. Some preserve story elements such as surprise effect and otherness, while some preserve the readers’ immersion in the story. The procedures taken show that one needs to consider the context of each unit in translating and that not only one procedure can be applied as a panacea in translating every unit in a code-switching language pair.